Dermatitis Kontak Alergi Akibat Plester Penutup Luka: Sebuah Laporan kasus Jarang dan Tinjauan Literatur - Lukman Nur Rahman; Ilham Suripto Gani (MEDICINUS, 2026)
Introduction: The use of medical adhesives as postoperative wound dressings can lead to sensitization and subsequently trigger allergic contact dermatitis (ACD) due to exposure to various chemical components contained within these products.Case report: A 32-year-old woman presented with a reddish rash on the abdominal area surrounding her postoperative wound dressing, appearing approximately one week after undergoing laparotomy for a cystic ovarian neoplasm. The rashfirst developed two days after surgery, accompanied by burning, warmth, and pruritus. The lesions progressed into small fluid-filled vesicle-like eruptions. Clinical examination revealed erythematous macules with papules, milia-like vesicles and bullae, along with diffuse scaling that followed the outline of the surgical adhesive. The dressing used was Pharmafix®, which contains acrylate-based medical adhesive. Treatment consisted of cetirizine 10 mg, methylprednisolone 4 mg twice daily, and topical desoximetasone cream 0.25%.Discussion: The patient was diagnosed with ACD induced by acrylate-containing medical adhesives. The allergic reaction was triggered by chemical components within the adhesive, including diethyl-dithiocarbamate, tetrahydrofurfuryl acrylate,and 2-hydroxyethyl methacrylate. Acute management involved removal of the adhesive, gentle cleansing of the affected area, and short-term use of topical corticosteroid when indicated.